PENGEMBANGAN KAMPUNG BAMBU DESA MOJOREJO SEBAGAI SENTRA KERAJINAN BAMBU MELALUI PENERAPAN IPTEKS, PRODUKSI INOVASI, DAN PEMANFAATAN DIGITAL - Rusli, Lathiefa; Muslih, Mohammad; Utomo, Bambang Setyo; Alfadla, Maya Tsurroya; Diannita, Rindang; Aini, Nur (Universitas Mataram, 2024)
Each village has its own history and potential to be used as a basis for implementing village development and development, one of which is Mojorejo Village, Jetis District, Ponorogo Regency. In order to develop the potential of their region, the community plays an active role in utilizing regional assets in the form of bamboo plants to be processed into handicrafts. However, craftsmen face several problems, including the low quality and quantity of bamboo production in Mojorejo Village. Apart from that, the process of making bamboo crafts is quite long, making craftsmen complain of low back pain, which can stop the process of making crafts. The ABCD method is used in this PKM journal as a more objective approach to what constitutes an asset in an area and its development. The results obtained are that in developing Mojorejo Village into a bamboo village, there needs to be socialization activities, training and assistance as well as training for all stakeholders including the community (as bamboo craftsmen), the management of Bamboe Village and Studio Deling, as well as the participation of the Mojorejo Village Government to support the continued development of Village potential.